Chemical Blockage of the Mitochondrial Rhomboid Protease PARL by Novel Ketoamide Inhibitors Reveals Its Role in PINK1/Parkin-Dependent Mitophagy - Poláchová, Edita; Bach, Kathrin; Heuten, Elena; Stanchev, Stancho; Tichá, Anežka; Lampe, Philipp; Majer, Pavel; Langer, Thomas; Lemberg, Marius K; Stříšovský, Kvido (Journal of medicinal chemistry, 2023)
The mitochondrial rhomboid protease PARL regulates mitophagy by balancing intramembrane proteolysis of PINK1 and PGAM5. It has been implicated in the pathogenesis of Parkinson's disease, but its investigation as a possible therapeutic target is challenging in this context because genetic deficiency of PARL may result in compensatory mechanisms. To address this problem, we undertook a hitherto unavailable chemical biology strategy. We developed potent PARL-targeting ketoamide inhibitors and investigated the effects of acute PARL suppression on the processing status of PINK1 intermediates and on Parkin activation. This approach revealed that PARL inhibition leads to a robust activation of the PINK1/Parkin pathway without major secondary effects on mitochondrial properties, which demonstrates that the pharmacological blockage of PARL to boost PINK1/Parkin-dependent mitophagy is a feasible approach to examine novel therapeutic strategies for Parkinson's disease. More generally, this study showcases the power of ketoamide inhibitors for cell biological studies of rhomboid proteases.
Keywords: mitofagie; endopeptidasy; Metalloproteases; proteasy; Protein Kinases; lidé; Peptide Hydrolases; Mitophagy; Mitochondrial Proteins; Endopeptidases; proteinkinasy; metaloproteasy; Parkinsonova nemoc; ubikvitinligasy; Ubiquitin-Protein Ligases; mitochondriální proteiny; Parkinson Disease; Humans